A systematic review on an optimal dose of disaster preparedness intervention utilizing health belief model theory - Mhd Noor, Mohd Tariq (Universiti Putra Malaysia Press, 2022)
Disaster preparedness is an issue that receives little attention in the community. Communities must take preventative measures to overcome obstacles and improve community preparedness. This review identifies the optimal dose of disaster preparedness intervention in the community. A systematic literature search was conducted to examine a study about the optimal dose of disaster preparedness intervention developed for implementation at a community level. A scoping review based on the PRISMA diagram was conducted from four databases. A combination of keywords was adapted for each database. Inclusion and exclusion criteria were applied. A total of eight articles were synthesized based on the intervention dose of disaster preparedness among community interventions. The summarized studies provided evidence that the optimal dose for disaster preparedness intervention in the community can be prevented with an educational intervention program with a minimal dosage of intervention. The Health Belief Model Theory was the most often cited theory by researchers. The best dose for disaster preparedness intervention in a community can be mitigated with a single dose of education. Nonetheless, we cannot disregard alternative disaster preparedness theories because each has its advantages and disadvantages.